Provenance variation of wild Hevea germplasm in a dry sub humid region of India - Krishan B; Nazeer M A; Rao G P; Rao K N (Indian Forester, 2011)
An evaluation at nursery stage of 56 wild accessions of 3 provenances of Amazon basin, Acre (AC), Rondonia (RO) and Mato Grosso (MT) of wild Hevea brasiliensis (Para Rubber) and 2 rubber commercial clones was carried out at the Regional Research Station of Rubber Research Institute of India located at Sukma, a drought prone area under dry sub humid region of Baster district in central-eastern India to obtain information about potential of variability in quantitative traits. Among the different accessions, girth ranged from 3.84 cm (AC 685) to 8.0 cm (RO 876), scion height 133.4 cm (AC 158) to 292.37 cm (RO 897), number of leaves 11.0 (AC 623) to 51.75 (RO 876) and leaf area from 85.49 cm2 (MT 58) to 195.60 cm2 (AC 623). The observations revealed wide inter and intra provenance variations for all the quantitative traits. The existance of high variability was evidenced by moderate to high estimates of phrnotypic and genotypic coefficient of variation for the traits. High heritability was observed for girth and scion height. Among the three provenances, Rondonia exhibited superiority for most of the traits. A judicious selection of these promising diverse materials would be useful in future bredding programmes.
Keywords: Heritability; Hevea; Provenance; Variability; Wild germplasm